Multi-omic characterization of bifunctional peroxidase 4-coumarate 3-hydroxylase knockdown in Brachypodium distachyon provides insights into lignin modification-associated pleiotropic effects - Shrestha, Him K.; Fichman, Yosef; Engle, Nancy L.; Tschaplinski, Timothy J.; Mittler, Ron; Dixon, Richard A.; Hettich, Robert L.; Barros, Jaime; Abraham, Paul E. (Frontiers in Plant Science, 2022)
A bifunctional peroxidase enzyme, 4-coumarate 3-hydroxylase (C3H/APX), provides a parallel route to the shikimate shunt pathway for the conversion of 4-coumarate to caffeate in the early steps of lignin biosynthesis. Knockdown of C3H/APX (C3H/APX-KD) expression has been shown to reduce the lignin content in Brachypodium distachyon. However, like many other lignin-modified plants, C3H/APX-KDs show unpredictable pleiotropic phenotypes, including stunted growth, delayed senescence, and reduced seed yield. A system-wide level understanding of altered biological processes in lignin-modified plants can help pinpoint the lignin-modification associated growth defects to benefit future studies aiming to negate the yield penalty. Here, a multi-omic approach was used to characterize molecular changes resulting from C3H/APX-KD associated lignin modification and negative growth phenotype in Brachypodium distachyon. Our findings demonstrate that C3H/APX knockdown in Brachypodium stems substantially alters the abundance of enzymes implicated in the phenylpropanoid biosynthetic pathway and disrupt cellular redox homeostasis. Moreover, it elicits plant defense responses associated with intracellular kinases and phytohormone-based signaling to facilitate growth-defense trade-offs. A deeper understanding along with potential targets to mitigate the pleiotropic phenotypes identified in this study could aid to increase the economic feasibility of lignocellulosic biofuel production.